Nietzsche’s Homo Natura and Biopolitics: Steps Towards an Ethical Reading (Balthazar, 2024)
The controversial figure of homo natura has recently been a central issue in Nietzsche’s studies. The debate regarding Nietzsche’s biopolitical character has taken homo natura to be a fundamental concept in order to assess his stand in political philosophy. In the following article several readings of homo natura will be presented and evaluated. The main thesis of this contribution is that this Nietzschean figure is best interpreted primarily in an “ethical” sense, namely, as a way of being and behaving. The political dimension is a consequence of this “ethical” posture and defies any easy biopolitical labeling. It is claimed that Nietzsche’s homo natura broadens the biopolitical discourse rather than taking place as one of its figures (as, e.g., Michel Foucault’s homo oeconomicus or Giorgio Agamben’s homo sacer) by explicitly addressing and overcoming the anthropocentric challenge that resides at the core of biopolitics. If we are right, then, depending on which homo natura’s interpretation we favour, we are left with a different categorization of Nietzsche’s political philosophy. Therefore, homo natura presents a cluster of questions that need to be addressed if we want to be able to fully grasp Nietzsche’s practical philosophy.